Propuesta de utilización turística de los Mogotes de la Sierra de los Órganos y el Pan de Guajaibón, Pinar del Río, Cuba. - Luis López, M.; Martín Hernández, J.; Acosta Hernández, M. R. (Geographicalia, 2016)
In order to maintain all the values of this area, "Mogotes de la Sierra de los Órganos" some of the most conserved of Cuba, this paper presents a proposition of management categories for them, according to Cuban National System of Protected Areas. With this proposition this hummocks, famous in the world, will be protected and incorporated to the national turistic economy.